Life is a meatloaf sandwich!: A devotional for early teens - Larsen, Carolyn; (1950-...) (U.S.A, 1995)
(3z(BLife is a meatloaf of sandwich(3y (Bwill take you through 365 days of real-life-could-be-talkin$1 (B-about-you stories paired with Bible passages that:s
Keywords: Life is a meatloaf sandwich